Mechanistic study on mechanical strengthening in As-extruded Mg-xSn (x = 0.5, 2, 4, 6 and 8 wt%) alloys - Song, Tingting; Yang, Fu; Niu, Xiaowei; Jia, Zheng (Frontiers in Materials, 2025)
This study systematically investigates the influence of Sn content (0.5–8 wt%) on the microstructural evolution and mechanical properties of as-extruded Mg-Sn alloys. By combining characterization techniques (XRD, scanning electron microscopy, EDS, and electron backscatter diffraction) with valence electron theory, the fundamental deformation mechanisms were elucidated. The results reveal that Sn content significantly modulates the distribution of Mg2Sn phases, dynamic recrystallization behavior, and deformation modes. The increase of Sn content has no obvious effect on the grain size, but the area fraction of Mg2Sn phase increases. The Mg-Sn bonds show the highest bonding energy among all possible atomic interactions, leading to enhanced mechanical properties. The alloy with 8% Sn demonstrates an optimal strength-ductility balance, due to grain refinement and strong texture effects. Furthermore, low-Sn alloys (≤2 wt%) deform primarily via basal slip, exhibiting ductile fracture characteristics, while high-Sn alloys (≥6 wt%) transition to a mixed fracture mode involving twinning and non-basal slip, attributed to increased Mg2Sn phase content.